Perbandingan Rasio PT Astra International, PT Gajah Tunggal, PT Indospiring, Dan PT Astra Otoparts Tahun 2020-2022 - Elmiano A. E. Erong; Rafi Adyatma; Ahmad Qois; Krisogonus A. Seleman; Cholis Hidayati (Jurnal Mutiara Ilmu Akuntansi, 2024)
The aim of this research is to analyze the comparative ratio of PT Astra International, PT Gajah Tunggal, PT Indospiring, and PT Astra Otoparts for 2020-2022. The type of research carried out was qualitative with secondary data sources from the IDX. The population in this study were automotive companies listed on the IDX and four of them were selected as samples. The results of this research show that Astra Otoparts and Indospring have the best liquidity ratio values, then for the activity ratio the company that has the best value is Astra Otoparts. Meanwhile, in terms of profitability ratios, the companies that have good scores are Indospring and Astra Otoparts, then in terms of profitability ratios and market ratios the company that has the best ratios is Astra Otoparts.